Pengaruh Marketing Mix Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Produk Minuman Mixue Cabang Mojosari - Adita Adita; Rama Rama; Nersiwad Nersiwad; Budi Utami (Lembaga Pengembangan Kinerja Dosen, 2023)
The development of franchise businesses in the field of f&b is a form of human innovation and creativity as we live in modern times and this has led to high competition. This competition makes business actors implement marketing strategies with the aim of attracting consumers through purchasing decisions. This study aims to determine the effect of Marketing Mix and Service Quality on Purchase Decisions for Mixue beverage products in the Mojosari branch. This study used a quantitative method with a sample of 100 respondents using accidental sampling technique. The data collection method used online questionnaires and used data processing tools in the form of IBM SPSS 26. The results showed that marketing mix and service quality had a positive and significant effect on purchasing decisions at Mixue outlets Mojosari branch.